Computer Aided Design of Semi-Submersibles for Deepwater Operations - Khamis, Nur Syaheerah (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Current selection work for offshore floaters typically engaged to detail calculations and scaled-model testing. Design library for offshore floaters may ease the design and selection process by providing instant result for basic performance analysis of the floaters. The project “Computer Aided Design of Semi-submersibles for Deepwater Operations” is a project made in order to improve the work made in previous projects on offshore platforms libraries. The main objective of this project is to improve the variation of the semi-submersibles model platform from previous project and also to evaluate the performance of the semi-submersible using parameters chosen. A proper research work has been made before specifying any design criteria and parameters. The scope of work of the study is to develop the hull section for semi-submersible model of six-column twin-pontoon. The design of the floaters and the libraries are developed using CATIA V5R20 with focusing on the vertical center of gravity and draft of the floater. The performance of the semisubmersibles is supported using established numerical methods and calculations. The results are divided to three components of the semi-submersibles floater and its individual stability analysis. As a conclusion, this project is the improved version of currently existed offshore floaters design library and may be a stage for any future library enhancement.